The dead trickster and his shrewd children? The persuasive use of the double quotations of a dead patriarch in Genesis 49 29-50:21 - Michael, Matthew (2018)
Biblical narrative is typically populated with characters who skilfully quote, misquote, or even distort the words of other characters. However, it is often rare in these biblical quotations to find the quotation and manipulation of the speeches of a dead character. Significantly, Genesis 49:29-50:21 describes the double quotations of a dead patriarch-Jacob-and the artful use of his quoted words for persuasive purposes by both Joseph and his brothers. In particular, the study engages the presence of stylistic changes, omissions, and even fabrications in these double quoted speeches of this trickster par excellence. In this way, it seems Jacob-even though now dead-continues to live once more in these scenes of quoted speeches.
Keywords: Bibel; Dead character; Genesis; Narrative; Persuasion; Quotation; Trickster